Self-absorption in "Urban Urbanism" as an answer to the limitations of territorial planning (Ciudades, 2018)
The implicit difficulties on the global project of city and the voluntary configuration of metropolitan transformations, have generated a pendulum movement that negates the possibility -and even the convinience- of such a project; the alternative would revolve around reducing its content to the fragmentary design of concrete urban pieces. There has been an understandable return towards the safe channels of the strict architectural and projectual disciplinarity, that has nothing to do with "economicist", "sociologist" or "political" pollutions and that claim the purity of design and the conception of city as a mere acumulation of architectures of better or worse quality.
Keywords: global project of city; urban urbanism